Effect of Etching Strategy (HF vs. In Situ HF via LiF/HCl) on Structural Properties and Adsorption Performance of TiCT MXene for Reactive Blue 221 Removal - Gozet, Nurullah; Celik, Aytekin (Springer, 2026)
This study systematically evaluated Ti3C2Tx MXene adsorbents synthesized via conventional HF etching and a milder LiF/HCl in situ HF generation route for the removal of Reactive Blue 221 (RB221) from aqueous solutions. Adsorption performance was compared under varying operational conditions, including pH, temperature, adsorbent dosage, and initial dye concentration, together with kinetic, isotherm, thermodynamic, and structural analyses. Results showed that LiF/HCl-etched Ti3C2Tx consistently outperformed the HF-etched counterpart. At optimized conditions (pH 2, 60 degrees C), the LiF/HCl-derived MXene achieved nearly complete dye removal (similar to 95-100%) with rapid equilibrium within 10-20 min, while HF-etched samples showed lower efficiency (< 70%) and slower kinetics. The maximum adsorption capacity reached 145 mg g(-1) for LiF/HCl, compared to 100 mg g(-1) for HF-etched material. Kinetic modeling indicated that adsorption follows a pseudo-second-order model (R & sup2; > 0.99), suggesting chemisorption. Isotherm analysis fit the Langmuir model well for LiF/HCl samples (R & sup2; = 0.9994), indicating monolayer adsorption on a homogeneous surface. Thermodynamic parameters confirmed the process is spontaneous and endothermic, with improved adsorption at higher temperatures. Characterization (XRD, SEM, XPS, TGA) revealed increased interlayer spacing, better exfoliation, and higher surface functional groups (-OH/-O) in LiF/HCl-etched MXene. These features enhance electrostatic attraction, hydrogen bonding, and pi-pi interactions with RB221 molecules. Overall, the superior performance of LiF/HCl-etched Ti3C2Tx is attributed to its improved surface chemistry and morphology, highlighting the importance of etching strategy in tailoring MXene materials for efficient wastewater treatment applications.
Keywords: Adsorption; Reactive Blue 221 Dye; Etching Strategy (Hf Vs Lif/Hcl); Ti3C2Tx Mxene